Răspunsuri

2014-10-21T11:08:52+03:00
a)a-b=18, b-c=11 si a+c=57

a-b=18  a=18+b
b-c=11
18+b+c=57
----------------------
b-c+18+b+c=11+57
18+2b=68
2b=68-18
2b=50
b=50:2
b=25

b-c=11
25-c=11
c=25-11
c=14

a+c=57
a+14=57
a=57-14
a=43





b)a-b=9, b-c=3 si a+c=34


a-b=9  a=9+b
b-c=3
9+b+c=34
-------------
b-c+9+b+c=3+34
9+2b=37
2b=37-9
2b=28
b=28:2
b=14

a-b=9
a-14=9
a=9+14
a=23

a+c=34
23+c=34
c=34-23
c=11








2014-10-21T11:28:27+03:00
A-b+b-c=18+11
a-c=29
a+c+a-c=57+29
2a=86
a=43

a-b=18
43-b=18
b=25
                                            

b-c=11
c=25-11
c=14